Recursos didácticos concretos y virtuales para la enseñanza de Movimiento y Fuerza en primer año de Bachillerato General Unificado - Maldonado Machuca, María Emilia (2023)
Concrete and virtual didactic resources enhance significantly the abstraction of complex concepts presented in the subject of Physics. In this sense, the objective of this research was to analyze the importance of didactic resources in the teaching of Movement and Force in the first year of General Unified High School. For this purpose, an exploratory-descriptive study based on a mixed approach was carried out. The literature review provided the basis for the conceptual categories, and the field review made it possible to determine the most appropriate concrete and virtual didactic resources to strengthen teaching practice in the teaching of Movement and Strength. The main results show that didactic resources are important in the teaching of Movement and Strength because: they allow abstraction, motivate learning, facilitate teaching, allow the theory-practice relationship, and enhance education. In addition, it was determined that the most appropriate concrete teaching resources according to the teaching practice are the blackboard, the calculator, and printed materials; while virtual teaching resources include Google Classroom, slides, Fisicalab, GeoGebra, MinEduc resources and PhET. Consequently, it is convenient for teachers to know about both concrete and virtual didactic resources to enhance the teaching of Movement and Force in the subject of Physics. Keywords: Concrete didactic resources, virtual didactic resources, teaching-learning, Physics, didactic innovation.